Diksi Laki-laki dan Perempuan Dalam Puisi Mutahir Indonesia (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
Men and women use language diferently. Why? The simplest answer is because they differ sexually—something believed to be unchanged in our society. Then, is it true that there is a difference in the use of language between men and women? Are there really 'male' and female languages? Is it true that 'male' diction is identical with violence and 'female' diction with tendemess? Do we still believe that 'female' language is 'lower, as it deals with the patterns of weakness, than male' language which is 'stronger’?In terms of these uses of language by men and women, it is undeniable that so far, especially in valuing the works of literature, they are often seen subjectively and based more on names, on the person who created the works, and even on the gender, but not the works. It is also true that many literary works written by women tend to be seen from gender point of view. Considering this tendency this paper will seek to find out whether this difference in the use of language by men and women in literary works, especially in contemporary Indonesia poetry. The paradigm used here is that gender differences in the use of language may be less than what is usually accepted as reality. However, it can also seen here that sosiolinguistic approach does not focus on narrative, but on the ideology of the narrator.Therefore, the discussion in this paper will focus more on the diction of poetry, which is closely related with the nature of the language of poetry, which is dens with meanings. The words selected by a poet are the most suitable words into context of the poetry. Replacing the words in the lines of a poem with other poetry will not be seen as something independent, but as something in a broads context considering that a work of literature is a solid discourse.